2013
DOI: 10.1051/matecconf/20130601002
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation into the influence of specimen size, in-situ pore pressures and temperatures on the spalling of difference size concrete panels when exposed to a hydrocarbon fire

Abstract: Abstract. Small and large scale reinforced concrete panels/walls were tested under hydrocarbon fire conditions to investigate concrete spalling. Results indicated that spalling is caused by the combination of thermal stresses and pore water pressure build-up. The degree and magnitude of spalling is governed by a number of inter-dependent factors including panel size, thickness and compressive strengths, all of which are investigated in this research. High strength concrete panels of increased surface area and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Regarding the effect of aggregate shape on the occurrence probability of concrete spalling due to fire, concrete with crumpled aggregates is further susceptible than spherical aggregate when it comes to spalling [141]. Moreover, spalling is even more severe in thicker and more significant concrete panels with high strength [142]. According to a study, different sized heated concrete spheres break apart in unique ways; that is, the size of the concrete element plays a role in the concrete spalling pattern [143].…”
Section: -400mentioning
confidence: 99%
“…Regarding the effect of aggregate shape on the occurrence probability of concrete spalling due to fire, concrete with crumpled aggregates is further susceptible than spherical aggregate when it comes to spalling [141]. Moreover, spalling is even more severe in thicker and more significant concrete panels with high strength [142]. According to a study, different sized heated concrete spheres break apart in unique ways; that is, the size of the concrete element plays a role in the concrete spalling pattern [143].…”
Section: -400mentioning
confidence: 99%
“…Heat induced spalling phenomena remain relatively poorly understood from a fundamental perspective [Maluk, 2014] and depend on a large number of factors, including the geometry of the concrete elements and the externally applied loads [Guerrieri and Fragomeni, 2013;Jansson and Bostrom, 2013;Carre et al, 2013]. Other factors influencing spalling are discussed in Section 2.2.3.…”
Section: Tunnelsmentioning
confidence: 99%
“…Further six TCs (No. [11][12][13][14][15][16] were fixed at the rear side of the specimen (Figure 2). The detailed positions of all TCs are given in Table III.…”
Section: Heat Investigationmentioning
confidence: 99%
“…Several studies solely showed the occurrence of spalling while others have quantified spalling by factors such as weight loss, number of spalling events, spalling depth or spalling volume. The latter ones were usually determined by extensive measurements after fire testing, for example by using a surface scanner [10,11]. Moreover, concrete properties such as strength, density or permeability have been widely used to predict the risk of spalling (e.g., [9,12]).…”
Section: Introductionmentioning
confidence: 99%